TECHNOLOGIES FOR USING NATIONAL VALUES IN THE SPIRITUAL AND MORAL EDUCATION OF OLDER PRESCHOOL CHILDREN (International journal of artificial intelligence, 2025)
The integration of national values into the spiritual and moral education of preschool children is a vital process in the formation of their identity, character, and worldview. In the context of globalization and digital transformation, it becomes increasingly important to use innovative pedagogical technologies to instill national values effectively. This paper explores the essence of national values and their role in the upbringing of preschoolers, emphasizing the technological and methodological means of their implementation. By analyzing various pedagogical approaches, digital tools, and interactive methods, the research outlines practical strategies for educators to create a value-oriented educational environment that nurtures patriotism, respect for cultural heritage, and social responsibility among older preschool children.